Reconstructing ancient Korean history : the formation of Korean-ness in the shadow of history - Xu, Stella (Lanham : Lexington Books, 2016)
"This book examines the historiography of ancient Korea and its relationship to the construction of Korean national identity through a critical and comparative analysis of Chinese and Korean primary sources. It also analyzes the ways in which Korean politics and culture have shaped and been affected by historical narratives"--Provided by publisher
From others to barbarians : the conceptualization and evolution of Yi -- Negotiating the past, reinterpreting ancient history : legitimacy in the lineage of ancient Korean history -- Ancient history reinvented : another battleground for national prestige and political legitimacy -- From a Marxist universal history to an ultra-nationalist approach : studies on ancient history in North Korea -- In the name of history : laying claim to the historical sovereignty of Manchuria (Northeast China) -- Conclusion: Living with the legacy of the past.
Includes bibliographical references (pages 209-219) and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Gug lib mun hwa jae yeon gu so; Korea -- History -- To 935 -- Historiography; Historiography -- Political aspects -- Korea -- History; Nationalism -- Korea -- History; National characteristics, Korean -- History; Politics and culture -- Korea -- History; Korea -- History -- To 935 -- Sources; Corée -- Histoire -- Jusqu'à 935 -- Historiographie; Nationalisme -- Corée -- Histoire; Coréens -- Histoire; Politique et culture -- Corée -- Histoire; Corée -- Histoire -- Jusqu'à 935 -- Sources; Historiographie -- Aspect politique -- Corée -- Histoire; HISTORY -- Asia -- China; Historiography; Historiography -- Political aspects; National characteristics, Korean; Nationalism; Politics and culture; Korea; Geschichtsschreibung; Nationalbewusstsein; China; Koguryŏ; To 935; History; Sources